The Role of Corporate Social Responsibility and Intellectual Capital on Company Value in the Banking Sector - Sari, Eliza; Meirina, Elsa (Institut Bisnis dan Informatika Kesatuan, 2023)
Company value is an important condition which is the main object for the company to continue to produce and increase company value as a continuation of the company's life in the future. This research aims to determine the influence of corporate social responsibility and intellectual capital on company value with good corporate governance as a moderating variable in the banking sector for the 2018-2022 period. The research method used is a quantitative method. The data collection technique used in this research is purposive sampling. The research samples were banking companies registered on the IDX with the number of samples used being 36 companies with a total of 5 years of research so that the final data used was 180 data. The research data analysis method uses Partial Least Squares (PLS) using the SmartPLS 4.0 application. The research results show that Corporate Social Responsibility (CSR) has no effect on company value. Likewise, Intellectual Capital (IC) has no effect on company value. In addition, Good Corporate Governance (GCG) does not moderate the relationship between CSR and company value, as well as between IC and company value.